2014
DOI: 10.5194/acp-14-5959-2014
|View full text |Cite
|
Sign up to set email alerts
|

Cloud condensation nuclei (CCN) activity of aliphatic amine secondary aerosol

Abstract: Abstract. Aliphatic amines can form secondary aerosol via oxidation with atmospheric radicals (e.g., hydroxyl radical and nitrate radical). The particle can contain both secondary organic aerosol (SOA) and inorganic salts. The ratio of organic to inorganic materials in the particulate phase influences aerosol hygroscopicity and cloud condensation nuclei (CCN) activity. SOA formed from trimethylamine (TMA) and butylamine (BA) reactions with hydroxyl radical (OH) is composed of organic material of low hygroscopi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
(53 reference statements)
2
14
2
Order By: Relevance
“…The evaporation of organics inside the CCN column, resulting in shrinking of aerosol particles at high temperature difference (higher SS), could also cause different κ at different supersaturations [ Asa‐Awuku et al ., ; Tang et al ., ]. However, this would cause a lower κ at higher supersaturation due to more efficient evaporation at higher temperature used at higher supersaturation, which is opposite to the finding in this study.…”
Section: Resultscontrasting
confidence: 93%
“…The evaporation of organics inside the CCN column, resulting in shrinking of aerosol particles at high temperature difference (higher SS), could also cause different κ at different supersaturations [ Asa‐Awuku et al ., ; Tang et al ., ]. However, this would cause a lower κ at higher supersaturation due to more efficient evaporation at higher temperature used at higher supersaturation, which is opposite to the finding in this study.…”
Section: Resultscontrasting
confidence: 93%
“…Low molecular weight amines are commonly found in the atmosphere in both gas and particle phases (Ge et al, 2011a, b). Based on present theoretical calculations (Kurtén et al, 2008;Loukonen et al, 2010;Paasonen et al, 2012;Olenius et al, 2017), laboratory simulations (Wang et al, 2010a, b;Kurtén et al, 2014;Erupe et al, 2011;Almeida et al, 2013;Yu et al, 2012) and field observations (Smith et al, 2010;Kürten et al, 2016;Tao et al, 2016), amines in the atmosphere have been proved to play an important role in new particle formation and subsequent particle growth and thus affect both the number concentrations of aerosols and cloud condensation nuclei that are closely relevant to regional climate (Tang et al, 2014;Yao et al, 2018). For example, dimethylamine (DMA) was found to be a key species involved in new particle formation events in the urban area of Shanghai, and the nucleation mechanism was likely to be H 2 SO 4 -DMA-H 2 O ternary nucleation .…”
mentioning
confidence: 89%
“…Zheng et al (2015) measured an average concentration 7.2 ppt of total amines in a suburban site of Nanjing during the summer of 2012, derived mainly from industrial emissions in adjacent areas. The aminiums in fine particles over Shanghai in the summer of 2013 were found to exhibit a high concentration (mean 86.4 ng m −3 ) and play an important role in the new particle formation events (Tao et al, 2016). Previous studies on aminiums over the marginal seas off the coast of China indicated that DMAH + and trimethylaminium (TMAH + ) were overwhelmingly from marine sources Yu et al, 2016;Xie et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few previous atmospheric chamber studies investigating the oxidation of alkyl amines at room temperature (Malloy et al 2009a, Lee andWexler 2013;Price et al 2014;Tang et al 2014). These studies highlighted the presence and importance of salt formation, the formation of imines and carcinogenic nitramines, the formation of highly oxidized oligomers (trimethylamine experiments), and cloud condensation nuclei activity in secondary organic aerosol formation from alkyl amines.…”
Section: Introductionmentioning
confidence: 99%